First Detection of Aedes albopictus (Diptera: Culicidae) and Expansion of Aedes japonicus japonicus in Wisconsin, United States. Issue 1 (13th October 2018) - Richards, Thomas; Tucker, Bradley J; Hassan, Hassan; Bron, Gebbiena M; Bartholomay, Lyric; Paskewitz, Susan
Abstract: The 2015–2016 epidemic of Zika virus in the Americas raised concerns about the range of Aedes albopictus (Skuse) in the United States. In response, the University of Wisconsin Medical Entomology Laboratory coordinated with the Wisconsin Department of Health Services in 2016 to conduct Aedes spp. surveillance and set up an oviposition trap (ovitrap) network operated by local public health partners across southern and western Wisconsin. During 2016, 916 ovitrap events were processed, but only Aedes triseriatus Say (Diptera: Culicidae) and Aedes japonicus japonicus (Theobald) were detected. In 2017, a focused surveillance approach was employed to detect Ae. albopictus near sites with tires stored outdoors. Using this targeted approach, Ae. albopictus was detected from ovitraps in two out of seven counties surveyed during June, July, and August. This is the first record of Ae. albopictus in Wisconsin.